Відповідь:
1)(b-6)/(b-3)-b/(3-b)=2
2)(6с+4)/(7-с)+(3с+25)/(с-7)=-3
3)(3а+1)^2/(24a-24)+(a+3)^2/(24-24a)=(a+1)/3
4)(36-8x)/(x-6)^2-(4x-x^2)/(6-x)^2=1
Пояснення:
1)(b-6)/(b-3)-b/(3-b)=(b-6)/(b-3)+b/(b-3)=(2b-6)/(b-3)=2(b-3)/(b-3)=2
2)(6с+4)/(7-с)+(3с+25)/(с-7)=(3с+25)/(с-7)-(6с+4)/(с-7)=(3с+25-6с-4)/(с-7)=(-3с+21)/(с-7)=
(-3(с-7))/(с-7)=-3
3)(3а+1)^2/(24a-24)+(a+3)^2/(24-24a)=(9a^2+6a+1)/(24a-24)-(a^2+6a+9)/(24a-24)
=(9a^2+6a+1-a^2-6a-9)/(24a-24)=(8a^2-8)/(24(a-1))=(a^2-1)/(3(a-1))=(a-1)(a+1)/(3(a-1))
=(a+1)/3
4)(36-8x)/(x-6)^2-(4x-x^2)/(6-x)^2=(36-8x)/(x-6)^2-(4x-x^2)/(x-6)^2=(36-8x-4x+x^2)/(x-6)^2=
(x^2-12x+36)/(x-6)^2=(x-6)^2/(x-6)^2=1
log₂ sin(x/2) < - 1
ОДЗ: sinx/2 > 0
2πn < x/2 < π + 2πn, n ∈ Z
4πn < x < 2π + 4πn, n ∈ Z
sin(x/2) < 2⁻¹
sin(x/2) < 1/2
- π - arcsin(1/2) + 2πn < x/2 < arcsin(1/2) + 2πn, n ∈ Z
- π - π/6 + 2πn < x/2 < π/6 + 2πn, n ∈ Z
- 7π/6 + 2πn < x/2 < π/6 + 2πn, n ∈ Z
- 7π/3 + 4πn < x < π/3 + 4πn, n ∈ Z
2) log₁/₂ cos2x > 1
ОДЗ:
cos2x > 0
- arccos0 + 2πn < 2x < arccos0 + 2πn, n ∈ Z
- π/2 + 2πn < 2x < π/2 + 2πn, n ∈ Z
- π + 4πn < x < π + 4πn, n ∈ Z
так как 0 < 1/2 < 1, то
cos2x < 1/2
arccos(1/2) + 2πn < 2x < 2π - arccos(1/2) + 2πn, n ∈ Z
π/3 + 2πn < 2x < 2π - π/3 + 2πn, n ∈ Z
π/6 + πn < x < 5π/6 + πn, n ∈ Z